P297 Effect Of Bts-recommended Medical Leadership On The "door-to-mask" Time Of Acute Non-invasive Ventilation (niv) Set Ups. (10th November 2014) - Boryslawskyj, H; Rauf, F; Beauchamp, B; Oakes, A; Santana-Vaz, N; Chakraborty, B; Mukherjee, R
Abstract : Introduction: NIV is now part of standard acute care in the UK. "Door-to-mask" time has been discussed as a performance/quality indicator of acute NIV services [Mandal S et al . Thorax, 66(4). A117]. We compare the "Door-to-mask" time by analysing the "% of patients receiving NIV within 3 h" of diagnosis of acute hypercapnic respiratory failure (AHRF) at two acute hospitals in central England: Hospital A, which appointed a Lead NIV consultant in 2009–10 as per BTS recommendations and Hospital B without a Lead consultant. Both hospitals are run by the same Trust and on call physiotherapy teams, with comparable acute catchment sizes. Methods: The survey was approved as an audit by the Trust's Clinical Standards Committee. Data was taken from the acute NIV database, maintained continuously since 2004 at HospitalA and since 2009 Hospital B as part of a drive to maintain built-in quality. All acute NIV episodes between 01/10/2010–01/04/2011 (period 1) and 01/10/2012–01/04/2013 (period 2) were included: 458 episodes (27 excluded – incomplete data). Results: In period1, the "% of patients receiving NIV within 3 h" of diagnosis of AHRF were 69.9% at Hospital A and 69.49% at Hospital B. In period2, Hospital A improved to 82% with Hospital B at 71.1%. The most significant improvement, however, was in the reduction of variance around the median "Door-to-mask" time of 1.55 h at Hospital A and 1.83 h at HospitalB on the Probability Density curves, also seen over other periods outside the ones studied. Conclusions: The service at Hospital B did not show any measurable improvement in 'door-to-mask time' between periods1 and 2 but Hospital A did. As there were no significant differences like the demography, work load, frequency of on calls or number/grades of staff between the periods 1 and 2, this improvement could be a reflection on the role of a Lead NIV consultant at Hospital A as per BTS recommendations. Furthermore, reduction of variance around the median "Door-to-mask" time is observed to be a consistent feature of the improvement, which needs evaluation as an independent performance/quality indicator of acute NIV services.